Perceptual and Metabolic Responses During Resistance Training Sessions: Comparing Low-Load Plus Blood Flow Restriction with High-Load Plans - Macedo, Anderson Geremias [UNESP]; Massini, Danilo Alexandre [UNESP]; Almeida, Tiago André Freire [UNESP]; Santos, Adriana Teresa Silva; Galdino, Giovane; de Oliveira, David Michel; Filho, Dalton Muller Pessôa [UNESP] (MDPI, 2025)
This study analysed perceived exertion (RPE) and blood lactate ([La-]) responses to two resistance training protocols planned with high- (HLI) and low-load intensities combined with blood flow restriction (LLI+BFR). Fourteen trained adults (26.2 ± 2.6 years) performed the HLI and LLI+BFR protocols 48 h apart. The HLI was planned with 70% 1RM (one repetition to maximum), three sets, 12 repetitions, 60 seconds (s) of rest between sets and 120 s between exercises; LLI+BFR was performed at 30% 1RM, for three sets, 15 repetitions, and with 30 s of rest between sets and 180 s between exercises. Blood samples (for [La-] analysis) and RPE (Borg 0-10 scale) were collected in the first minute after each exercise. A two-way ANOVA compared RPE and [La-] responses between exercises in the same protocol, and between protocols comparing the same exercise. RPE increased from the first to the last half (involving upper-limbs and lower-limbs) of exercises in both protocols (p < 0.001). All exercises in HLI elicited higher RPE values than LLI+BFR (p < 0.001). Average RPE scores were higher in HLI than for LLI+BFR (8.1 ± 0.6 > 6.2 ± 1.1, p < 0.001). The [La-] also increased throughout the exercises, with a higher peak response in LLI+BFR than for HLI (9.8 ± 1.6 > 7.2 ± 1.3 mmol × L-1, p < 0.01). Perceptual and metabolic responses during HLI and LLI+BFR training were distinguishable, despite both protocols characterising a high-intensity stimulus.